The relationship between platelet to lymphocyte ratio and the clinical outcomes in ST elevation myocardial infarction underwent primary coronary intervention - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2014)
The platelet to lymphocyte ratio (PLR) has been investigated as a new predictor for cardiovascular risk. The aim of the present study was to investigate the prognostic role admission PLRat admission in predicting in-hospital and early mortality in patients presenting with ST segment elevation myocardial infarction (STEMI). A total of 639 consecutive patients with STEMI who underwent primary percutaneous coronary intervention (PCI) were included. The study population was divided into tertiles on the basis of PLR values at the admission. A high PLR (N=213) was defined as a value in the upper third tertile (PLR >174.9) and a low PLR (N=426) was defined as any value in the lower two tertiles (PLR 174.9). The patients were followed for clinical outcomes for up to 6 months after discharge. In Kaplan-Meier survival analysis, the rate of 6-month all-cause deaths was 7% in the high PLR group versus 3% in the low PLR group (P=0.03). In multivariate analyses, a significant association was noted between high PLR levels and the adjusted risk of 6-month all-cause deaths (odds ratio=2.51, 95% confidence interval=1.058-5.95; P=0.03). PLR is a readily available clinical laboratory value associated with 6-month all-cause death in patients with STEMI who undergo primary PCI.
Keywords: myocardial infarction; platelet count; prognosis; UNSTABLE ANGINA-PECTORIS; 3-YEAR FOLLOW-UP; ARTERY-DISEASE; INFLAMMATION; ASSOCIATION; NEUTROPHIL; PREDICTOR; MORTALITY; IMPACT; COUNT